Unusual cause of acute lower extremity ischemia in a healthy 15-year-old female: A case report and review of popliteal artery aneurysm management in adolescents - David M. Notrica; Emilie Amaro; Maria E. Linnaus; Jozef Zoldos (Elsevier, 2016)
Limb ischemia in healthy teenagers is unusual. While traumatic or iatrogenic injury is the most common etiologies of limb ischemia in the pediatric population, anatomic variants such as true aneurysms should be considered [1]. We report the second documented pediatric case of an idiopathic, isolated true popliteal aneurysm resulting in acute limb ischemia in a previously healthy 15-year-old female. We also review the proper evaluation and surgical management of this anatomic anomaly. In this case, surgical management included resection of the aneurysm, reconstruction with reverse saphenous vein grafting, and distal endarterectomies to restore adequate distal blood flow. Ultimately, this patient's limb and function were salvaged with minimal consequences.